PEMBELAJARAN KIMIA MODEL THINK-PAIR-SHARE DAN NUMBERED HEADS TOGETHER DITINJAU DARI KEMAMPUAN AWAL DAN AKTIVITAS BELAJAR - Priyani, N.E. (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2012)
Tujuan penelitian ini adalah untuk mengetahui: (1) Pengaruh pembelajaran kimia model TPS (Think-Pair-Share) dan NHT (Numbered Heads Together) terhadap prestasi belajar siswa. (2) Pengaruh kemampuan awal tinggi dan rendah terhadap prestasi belajar siswa. (3) Pengaruh aktivitas belajar tinggi dan rendah terhadap prestasi belajar siswa. (4) lnteraksi antara pembelajaran kimia model TPS dan NHT dengan kemampuan awal. (5) lnteraksi antara pembelajaran kimia model TPS dan NHT dengan aktivitas belajar siswa. (6) lnteraksi antara kemampuan awal siswa dengan aktivitas belajar siswa. (7) lnteraksi antara pembelajaran kimia model TPS dan NHT dengan kemampuan awal siswa dan aktivitas belajar siswa. Penelitian ini menggunakan metode eksperimen. Berdasarkan hasil penelitian dapat disimpulkan: (1) Tidak ada pengaruh pembelajaran kimia model TPS dan NHT terhc!.:::r; prestasi belajar siswa. (2) Ada pengaruh kemampuan awal tinggi dan rendah terhadap prestasi belajar siswa. (3) Ada pengaruh aktivitas belajar tinggi dan rendah terhadap prestasi belajar siswa. (4) Ada interaksi antara pembelajaran kimia model TPS dan NHT dengan kemampuan awal. (5) Tidak ada interaksi antara pembelajaran kimia model TPS dan NHT dengan aktivitas belajar siswa. (6) Tidak ada interaksi antara kemampuan awal siswa dengan aktivitas belajar siswa. (7) Tidak ada interaksi antara pembelajaran kimia model TPS dan NHT dengan kemampuan awal siswa dan aktivitas belajar siswa.The aims of this research were to find out: (1) the effect of Chemistry Learning using TPS (Think-PairÂ Share) and NHT (Numbered Heads Together) Models toward students achievement. (2) the effect of high and low prior knowledge toward students achievement. (3) the effect of high and low students activity toward their achievement. (4) the interaction between Chemistry Learning Models with prior knowledge toward students achievement. (5) the interaction between Chemistry Learning Models with students activity toward students achievement. (6) the interaction between students prior knowledge and students activity toward students achievement. (7) the interaction between Chemistry Learning Models, students prior knowledge and students activity toward students achievement. The research used experimental method. Based on the results of the research can be concluded that: (1) there was no effects of chemistry learning models to the students achievement. (2) there was an effect of high and low prior knowledge to the students achievement. (3) there was an effect of high and low students activity toward students achievement. (4) there was interactions between chemistry learning models and prior knowledge toward students achievement. (5) there was no interactions between chemistry learning models and the students activity toward students achievement. (6) there was no interactions between prior knowledge and the students activity toward students achievement. (7) there was no interactions between chemistry learning models, prior knowledge and the students activity toward students achievement.